Names validly published in Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Louis-René ‘Edmond’ Tulasne in 1857, with reference to names proposed in sched. by Hilsenberg and Bojer for two Malagasy species, and with notes on the type of the name K. tubiflora - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2023)
The French botanist Louis-René ‘Edmond’ Tulasne validly published three new names in Kalanchoe (Crassulaceae subfam. Kalanchooideae) in 1857. These are K. eriophylla, K. miniata, and K. floribunda, with the first two of these names being based on material that was collected more than 30 years earlier in Madagascar by Carl Hilsenberg and Wenceslas Bojer, who are jointly credited as having made the first significant plant collections in the interior of the island. The third name, K. floribunda, was published for a species from the Comoros, but is an illegitimate later homonym, for which a lectotype is designated here. The fourth species that Tulasne dealt with in his treatment of Malagasy kalanchoes was included under the name Bryophyllum calycinum, which is now regarded as a synonym of K. pinnata. In the past, Bryophyllum was sometimes accepted as a genus distinct from Kalanchoe, but at present it is treated as K. subg. Bryophyllum. The nomenclature of the three names published in Kalanchoe and the one treated in Bryophyllum by Tulasne is reviewed and discussed in a historical context. The type of the name K. tubiflora, which was collected during a British expedition that lasted from 1822 to 1826 to South and East Africa, is clarified.